O acordo Brasil-Santa Sé e as relações entre Estado, sociedade e religião = The Brazil-Holy See Agreement and Relations between State, Society and Religion - Giumbelli, Emerson (Ciencias sociales y religión, 2011)
The paper analyzes the “Agreement between the Federative Republic of Brazil and the Holy See concerning the legal status of the Catholic Church in Brazil,” in effect since 2010. In addition to tracking some aspects of the lawsuit and its impact, the document is viewed as a privileged access to the forms of recognition of “religious” in Brazil. In its wake, are still considered other legislative proposals and debates on religious education in public schools.